The Views Of Community Leaders On The Walimatul Tradition 'ursy In One Day And One Night In View Of The Perspective Of Maslahah Mursalah In Sub-districts Mandastana Barito Kuala Regency - Fadhil, Muhammad; Hasan, Ahmadi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2023)
Abstract: The holding of walimatul 'ursy in each community's traditions is different. There was a response from community leaders that the one-night walimatul 'ursy had the potential to disturb people from resting at night, which usually includes entertainment that brings harm. On the other hand, community leaders consider that the one-night wedding reception provides an opportunity for invited guests who are far away to be able to attend which brings benefits such as evening entertainment provided is shalawatan or cultural arts events. The purpose of this research is to find out what community leaders think about the day and night Walimatul 'Ursy event and to find out what Maslahah Murlah's perspective is regarding holding the day and night Walimatul 'Ursy. This research is empirical legal research. So, to obtain data in the Mandastana sub-district, Barito Kuala district, research was conducted on 10 community leaders as to what their opinions were regarding the walimatul 'ursy day and night in terms of maslahah murlah. The results of the research obtained are that the majority of people hold wedding receptions until the evening, this is a tradition that has been preserved from time to time. The factor that causes people to think like this is because the organizers of the walimatul 'ursy hold their events until the evening using a weton count, therefore it is not necessarily on holidays or Sundays that the walimah event and more invited guests come at night to attend, there are also administrative factors because they have received permission from the authorities, and geographical factors, the majority of the people living in several villages have the same culture in the walimatul 'ursy tradition. Abstrak: Penyelenggaraan walimatul 'ursy tiap tradisi masyarakat berbeda-beda, mendapat tanggapan dari tokoh masyarakat bahwa walimatul 'ursy sehari semalam berpotensi mengganggu masyarakat untuk istirahat ketika malam hari yang biasanya terdapat hiburan yang membawa mudarat, disisi lain tokoh masyarakat menganggap saat resepsi pernikahan sehari semalam ini memberi kesempatan pada tamu undangan yang jauh agar bisa berhadir yang membawa kemanfaatan seperti malam hari hiburan dibawakan adalah acara shalawatan atau kesenian kebudayaan. Penelitian ini terdapat tujuan untuk mengetahui bagaimana pendapat tokoh masyarakat terhadap acara walimatul 'ursy dalam waktu sehari semalam serta untuk mengetahui bagaimana tinjauan perspektif maslahah mursalah mengenai penyelenggaraan walimatul 'ursy sehari semalam tersebut. Penelitian ini merupakan penelitian hukum empiris. Sehingga untuk memperoleh data di kecamatan Mandastana kabupaten Barito Kuala, dilakukan penelitian kepada 10 tokoh masyarakat seperti apa pendapat mereka terhadap walimatul 'ursy sehari semalam dari segi maslahah mursalah. Hasil penelitian yang didapat yaitu sebagian besar masyarakat yang melaksanakan resepsi pernikahan sampai malam hari adalah tradisi yang dilestarikan dari zaman ke zaman. Faktor penyebab dari masyarakat beranggapan seperti demikian karena pihak penyelenggara walimatul 'ursy yang mengadakan acaranya sampai malam hari menggunakan hitungan weton, maka dari itu tidak tentu dihari libur atau minggu acara walimahnya dan tamu undangan lebih banyak datang pada malam hari untuk hadir, ada juga faktor administrasi karena dapat telah mendapat izin dari pihak berwenang, dan faktor geografis dari masyarakat yang mayoritas tempat tinggal pada beberapa desa memiliki kebudayaan yang sama dalam tradisi walimatul ‘ursy.